ANALYTICAL APPROACH TO EVALUATION OF THE STRUCTURAL CONDITION OF EXISTING PAVEMENT - Prayudyanto, Nanang
ANALYTICAL APPROACH TO EVALUATION OF THE STRUCTURAL CONDITION OF EXISTING PAVEMENTS, Prayudyanto, Nanang, 1989, Program Sistem dan Teknik Jalan Raya, Fakultas Pasca Sarjana, Institut Teknologi Bandung. Surface deflection parameters, e.g. maximum deflection and surface curvature index, are used to evaluate the structural adequacy of existing pavements on a direct diagnostic basis. Subsequently, from an empirical design method, the required overlay thickness is determined in such a way that the deflection is reduced to an extent required by the additional cumulative traffic loading to be carried by' the overlay. Unfortunately, applicability of any such method is limited to the geographical region where the method is developed and also to the overlay materials used. An analytical approach is inherently capable of assessing the structural parameters, i.e. the pavement modulus, on the basis of deflection data, pavement thickness and estimated subgrade modulus. Research has been undertaken in an attempt to develop an analytical overlay design method by employing the "Asphalt Institute program DAMA". Modification of the original program has been carried out in order to present the transverse deflection results which are normally confined to the longitudinal deflection measurement for a given pavement structure and loading condition. Subsequent procedures involved modelling the existing pavement as a single- or two-layered system and the overlay design as a two- or three-layered system. Charts for a single and two-layered system and tables for a three-layered system have been developed. Pavement and subgrade moduli for given deflection parameters resulting from the charts are found to be in close agreement with those obtained by Boussinesq, Hogg-Burmister and Rufford models, as appropriate. Examples of overlay design for real deflection data by employing the charts and the tables are presented. However, the correlation of the proposed overlay design procedure with conventional overlay design methods has not been attempted